The Potential of Halal Culinary Gastronomy, the Role of Cultural Identity of Muslim Women Vendors, and Creative Economy on the Increase of Tourist Visits at Suranadi Tourism Village - Putri Amalia Wardi; Baiq Dinna Widiyasti; I Nengah Dwiki Widya Karmadi; Laela Purnama; Komang Bintang Rastini Triutami (Universitas KH. Abdul Chalim Mojokerto, 2025)
Halal tourism has rapidly grown as one of the prominent global market segments, particularly in Muslim-majority countries. Suranadi Tourism Village in Lombok, West Nusa Tenggara, holds unique potential through its halal gastronomy, the cultural identity of Muslim women traders, and creative economy initiatives, which together attract domestic and international visitors. This study aims to analyze the influence of these three factors on tourist visits by employing a mixed method approach. The quantitative phase involved survey data from 395 tourists using a Likert scale (1–5), analyzed with PLS-SEM. The qualitative phase was conducted through in-depth interviews with 15 key and analyzed thematically. Quantitative results indicate that all constructs were valid (outer loading > 0.70) and reliable (α and CR > 0.70; AVE > 0.50). Qualitative findings reinforced these results, highlighting tourists’ appreciation for the legendary Suranadi satay, their higher trust in women wearing hijab, and their interest in creative attractions such as rafting. The study concludes that integrating halal gastronomy, cultural identity, and creative economy creates a competitive halal tourism ecosystem. These findings provide significant implications for strengthening halal tourism branding strategies in West Nusa Tenggara.